2015
DOI: 10.1021/bi501073v
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Quinolone CP-115,955 Against Bacterial and Human Type II Topoisomerases Is Mediated by Different Interactions

Abstract: CP-115,955 is a quinolone with a 4-hydroxyphenyl at C7 that displays high activity against both bacterial and human type II topoisomerases. To determine the basis for quinolone cross-reactivity between bacterial and human enzymes, the activity of CP-115,955 and a series of related quinolones and quinazolinediones against Bacillus anthracis topoisomerase IV and human topoisomerase IIα was analyzed. Results indicate that the activity of CP-115,955 against the bacterial and human enzymes is mediated by different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…15 Although clinically relevant fluoroquinolone antibacterials display low activity against the human type II enzymes, some members of this drug class cross over into mammalian systems and are potent poisons of human type II topoisomerases. 7, 10, 54–56 Because poisoning the human enzyme precludes the clinical use of these fluoroquinolones as antibacterial agents, it is important to assess the activity of gyrase-targeted drugs against the human enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…15 Although clinically relevant fluoroquinolone antibacterials display low activity against the human type II enzymes, some members of this drug class cross over into mammalian systems and are potent poisons of human type II topoisomerases. 7, 10, 54–56 Because poisoning the human enzyme precludes the clinical use of these fluoroquinolones as antibacterial agents, it is important to assess the activity of gyrase-targeted drugs against the human enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent investigation, the interaction of quinolones and type II topoisomerase of human and bacteria are mediated by different types of interactions. It was shown that the quinolones target the gyrase and topoisomerase-IV enzymes and inhibit bacterial growth [86]. These enzymes have the potential to fragment the cell genome, which is essential for cell survival and reproduction.…”
Section: Mode Of Action Of Quinolonesmentioning
confidence: 99%
“…In addition, molecular docking and simulation of such structures and different quinolone analogues will be helpful in modelling the interactions to help design new drugs [83,84,96,97,98,99,100]. Osheroff and coworkers provided most of the data about the interaction of quinolones and topoisomerases [16,45,73,77,81,82,86,101,102,103,104,105,106,107,108,109]. In a recent study, the quinolone structure was placed near the serine and acidic residues, but it was found that the amino acids were not close enough to mediate a direct binding to drugs.…”
Section: Interaction Of Quinolones With Topoisomerasesmentioning
confidence: 99%
“…RADAR/slot blots [e.g. (Kiianitsa and Maizels, 2013;Aldred et al, 2015;Quinones et al, 2015;Vaz et al, 2016;Mohni et al, 2019)] probed with a mAb that recognizes an epitope in the catalytic domain of PARP1 (anti-cat-PARP1) showed that PARP1-DNA adducts were induced by treatment of either K562 or GM639 cells with 5-aza-dC ( Figure 3B).…”
Section: Parpimentioning
confidence: 99%